Literatur Pembelajaran Fiqh di Pondok Pesantren Propinsi Banten - Kharlie, Ahmad Tholabi (Research and Development Institution, Darussalam Institute for Islamic Studies, 2019)
The tradition of yellow books is commonly associated with the pesantren tradition. It may become a differentiating factor when compared to other institutions. In the beginning of its emergence, learning process in pesantrens is usually limited to the materials of reading Qur’an (qirâ’ah al-Qur’ân) and worship law (fiqh ibadah). Nevertheless, due to the vast number of books penetrating to Banten, particularly initiated by Syeikh Nawawi al-Bantani, the study of Islamic law became more popular among scholars. As a result, there are many methods applied in learning process for yellow books. Furthermore, the discrepancy of education methods in pesantrens: traditional (salafi) and modern (khalafi), may lead to the emergence of the different uses of literature and methods. In salafi pesantrens, bandongan or sorogan method is mainly employed to read the conventional books, such as Fath al-Qarib, Fath al-Wahhab and Mahalli. On the other hand, khalafi pesantrens tend to develop Arabic as well as English skills as their assets to continue their study to upper education grades. In addition, salafi pesantrens mostly emphasize to study various normative books, such as Syafi’i’s work whereas khalafi pesantrens tend to be liberal and flexible, by reading Bidayah al- Mujtahid and Fiqh al-Sunnah.